Regulation of CX3CL1 Expression in Human First-Trimester Decidual Cells: Implications for Preeclampsia. (September 2019) - Huang, S. Joseph; Chen, Chie-Pein; Buchwalder, Lynn; Yu, Ya-Chun; Piao, Longzhu; Huang, Chun-Yen; Schatz, Frederick; Lockwood, Charles J.
C-X3-C motif ligand 1 (CX3CL1) mediates migration, survival, and adhesion of natural killer (NK) cells, monocytes, and T-cells to endothelial/epithelial cells. Aberrant numbers and/or activation of these decidual immune cells elicit preeclampsia development. Decidual macrophages and NK cells are critical for implantation, while macrophage-derived tumor necrosis factor-α (TNF-α), interleukin-1 β (IL-1β), and NK cell-derived interferon-γ (IFN-γ) are associated with preeclampsia development. Thus, serum and decidual levels of CX3CL1 from first-trimester pregnancy and preeclampsia-complicated term pregnancy were examined by enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry, respectively. The effects of incubating primary human first-trimester decidual cells (FTDCs) with estradiol + medroxyprogesterone acetate + either IL-1β or TNF-α and/or IFN-γ on CX3CL1 expression were also assessed by quantitative reverse transcription-polymerase chain reaction and ELISA. The inhibition of each signaling pathway with each kinase and nuclear factor κB (NFκB) inhibitors was evaluated by ELISA. Chemotaxis of CD56 bright CD16 − NK cells by various concentrations of CX3CL1 was evaluated. C-X3-C motif ligand 1 is expressed by both cytotrophoblasts and decidual cells in first-trimester decidua. C-X3-C motif ligand 1 expression is increased in term decidua but unchanged in first-trimester and term serum of patients with preeclampsia. Interferon-gamma and either IL-1β or TNF-α synergistically upregulated CX3CL1 expression in FTDCs. Coincubation with IL-1β or TNF-α or IFN-γ, mitogen-activated protein kinase kinase 1 and 2 (MEK1/2), c-JUN N-terminal kinase (JNK), and NFκB inhibitors suppressed CX3CL1 production. C-X3-C motif ligand 1 elicited concentration-dependent enhancement of CD56 bright CD16 − NK cell migration. In conclusion, the current study suggests that decidual cell-secreted CX3CL1 is involved in the later development of preeclampsia, whereas circulating CX3CL1 levels do not predict preeclampsia. Mitogen-activated protein kinase kinase 1 and 2, JNK, and NFκB signaling mediate IL-1β-, TNF-α-, and IFN-γ-induced CX3CL1 production by FTDCs.